2022
DOI: 10.3389/fgene.2022.1010272
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and morpho-physiological analyses of the tolerance and recovery mechanisms in seedling stage spring wheat under drought stress

Abstract: Drought is one of the complex abiotic stresses that affect the growth and production of wheat in arid and semiarid countries. In this study, a set of 172 diverse spring wheat genotypes from 20 different countries were assessed under drought stress at the seedling stage. Besides seedling length, two types of traits were recorded, namely: tolerance traits (days to wilting, leaf wilting, and the sum of leaf wilting), and recovery traits (days to regrowth, regrowth biomass, and drought survival rate). In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(45 citation statements)
references
References 72 publications
0
44
1
Order By: Relevance
“…Highly significant variation was found among genotypes in each population for all phenotypic traits scored [19,20]. In this study, a non-significant effect was found between the two markers and seedling traits of the WP.…”
Section: Seedling Stagecontrasting
confidence: 46%
See 2 more Smart Citations
“…Highly significant variation was found among genotypes in each population for all phenotypic traits scored [19,20]. In this study, a non-significant effect was found between the two markers and seedling traits of the WP.…”
Section: Seedling Stagecontrasting
confidence: 46%
“…SLW and DTW are tolerance traits that indicate water deficit on wheat leaves, while RB and DTR are recovery traits indicating the ability of plants to recover and form new shoots after prolonged drought stress [29]. All these traits are highly heritable, so they are very useful for selection to drought tolerance [19,20,29,30]. In the WP, the non-significant association between the two markers and the seedling traits under drought stress indicated that there was no effect on improving drought tolerance for those genotypes that had the target allele.…”
Section: Seedling Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drought and heat stress induced the expression pattern of most LEA-1 genes under different conditions as evaluated by qRT-PCR analysis. The tolerant genotypes can modify genes under drought stress more strongly than the more vulnerable upland cotton genotypes [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wheat breeding programs mainly focus on improving grain yield, biotic and abiotic stress, and end-use quality traits ( Sandhu et al, 2021c ; 2022 ). High-yielding varieties with broader adaptations are one of the primary goals of wheat breeders globally; however, this is hindered by limited knowledge and testing of the genetic material for different agronomic and abiotic stress traits ( Sallam et al, 2018 ; Langridge and Reynolds, 2021 ; Ahmed et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%